Pola Pengembangan Potensi Daerah Dalam Upaya Peningkatan Produk Domestik Regional Bruto Provinsi Gorontalo - Kalzum R Jumiyanti; Barmin R Yusuf (Universitas Muhammadiyah Sorong, 2020)
The objectives of this paper are to analyze economic growth through the GRDP (Gross Regional Domestic Product) figure which leaves a problem of regional disparity between districts/cities in Gorontalo Province and aims to identify potential sectors in districts/cities in Gorontalo. The analytical method used is location quotient, Klassen typology, Williamson analysis, and Gini ratio. The findings in this paper are where Gorontalo City is the center of economic activity, so it can be said that of the 17 (seventeen) Gorontalo provincial national income sectors, 15 (fifteen) of them are based sectors, 2 sectors are agriculture, forestry and the fisheries and mining and quarrying sector are not the basic sectors in Gorontalo City. Gorontalo City has 15 (fifteen) basic sectors, 3 (three) sectors that have the highest value for the base sector including the water supply sector, the sector of providing food and drinking accommodation, and the real estate sector. Another case with other districts that are hinterland areas for developed regions. High inequality in developed regions (Gorontalo City) and hinterland areas such as Gorontalo Regency, Bone Bolango Regency, North Gorontalo Regency, Boalemo Regency, and Pohuwato Regency are caused by backwash effects so that financially cannot focus on funding investment in its superior sectors. Leading sectors in Gorontalo Regency have 9 (nine) leading economic sectors, Bone Bolango Regency has 11 (eleven) leading economic sectors, North Gorontalo Regency has 6 (six) leading economic sectors, Boalemo Regency has 1 (one) leading economic sector and Regency Pohuwato has 6 (six) leading economic sectors.